A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae) - Puchalski, Mateusz; Giłka, Wojciech (Zootaxa, 2017)
A new species of the genus Cladotanytarsus Kieffer, 1921 and the small subgenus Lenziella Kieffer, 1922 is described from Southern Oregon, USA. The adult male of C. (L.) glaber Giłka et Puchalski, sp. nov., featuring tibial lobes armed with dense setae and a large globular swelling of the hypopygial inferior volsella, supports the recently defined systematic concept for Lenziella. This subgenus is known from seven species distributed in the Northern Hemisphere (1 European, 1 Palaearctic and 5 Nearctic), the males of which are included in an updated identification key.